Estimated average blood glucose level based on fructosamine level - de Oliveira Andrade, Luis Jesuino; Bittencourt, Alcina Maria Vinhaes; de Brito, Luiz Felipe Moreno; de Oliveira, Luís Matos; de Oliveira, Gabriela Correia Matos (Archives of Endocrinology and Metabolism, 2023)
To define the mathematical relationship between fructosamine levels and average glucose values. The study comprised laboratory data of 1,227 patients with type 1 or 2 diabetes mellitus. Fructosamine levels measured at the end of a 3-week period were compared against the average blood glucose levels of the previous 3 weeks. Average glucose levels were determined by the weighted average of the daily fasting capillary glucose results performed during the study period, and the plasma glucose measured in the same sample collected for fructosamine measurement. In total, 9,450 glucose measurements were performed. Linear regression analysis between fructosamine levels and average glucose levels showed that for each 1.0 μmol/L increase in fructosamine level there was a 0.5 mg/dL increase in average glucose level, as estimated by the equation . The coefficient of determination (r2 = 0.353492, p < 0.006881) allowed the calculation of the estimated average glucose based on fructosamine level. Our study demonstrated a linear correlation between fructosamine level and mean blood glucose level, suggesting that fructosamine levels can be a proxy for the average glucose level in assessing the metabolic control of patients with diabetes.